The propriety of liberty : persons, passions and judgement in modern political thought - Kelly, Duncan (Princeton University Press, 2011)
In this book, Duncan Kelly excavates, from the history of modern political thought, a largely forgotten claim about liberty as a form of propriety. By rethinking the intellectual and historical foundations of modern accounts of freedom, he brings into focus how this major vision of liberty developed between the seventeenth and the nineteenth centuries. In his framework, celebrated political writers, including John Locke, Montesquieu, Adam Smith, John Stuart Mill, and Thomas Hill Green pursue the claim that freedom is best understood as a form of responsible agency or propriety, and they do so.